Environmental Issues along Supply Chains of Multinational Organizations: The case of "The Coca-Cola Company" - Guttensohn, Andreas Josef (2010)
I am looking at how CSR is embedded into organizations and governance processes, particularly in the multinational supply chain context. I previously did some work on Coca-Cola’s commitment to sustainable development and its commitment to achieve water neutrality. In my management project I would like to draw upon my original findings and extend them in 2 ways: